PENGEMBANGAN MODUL AJAR BERBASIS GUIDED INQUIRY BERBANTUAN GEOGEBRA TERHADAP KEMAMPUAN PEMAHAMAN KONSEP PESERTA DIDIK - Aisyah; Eva Margaretha saragih (Smart Education, 2026)
The study aims to develop a guided inquiry-based teaching module assisted by GeoGebra on the Conceptual Understanding of Quadratic Functions at Xth grade Students of Mas Al-Mukhlisin Tanjung Tiram. This research is a Research and Development (R&D) study using the 4-D development model, which includes the stages of Define, Design, Development, and Disseminate. The instruments used in this study include validation, teacher and student response questionnaires, and a conceptual understanding test. Based on the validator's assessment results, the developed open module obtained a validity value of 86%, categorized as very valid. The results of the practicality of the teaching module based on the teacher's response questionnaire were 100% and students were 83,17%, categorized as very practical. Meanwhile, the effectiveness of the teaching module, as seen from the concept comprehension ability test, obtained a value of 80%, categorized as effective. Thus, the guided inquiry-based teaching module assisted by GeoGebra on the quadratic function material at Xth grade is declared suitable for use in learning because it has met the criteria of valid, practical, and effective.